Characteristics and treatment of new-onset arthritis after checkpoint inhibitor therapy. Issue 2 (17th August 2018) - Leipe, Jan; Christ, Lisa A; Arnoldi, Andreas P; Mille, Erik; Berger, Frank; Heppt, Markus; Goldscheider, Ilana; Kauffmann-Guerrero, Diego; Huber, Rudolf M; Dechant, Claudia; Berking, Carola; Schulze-Koops, Hendrik; et al.
Abstract : Immune checkpoint inhibitors (ICIs) may cause immune-related adverse events (IRAEs). Characterisation and data on treatment of musculoskeletal IRAEs are scarce. In this cohort study, patients receiving ICI therapy who experienced arthralgia were evaluated for the presence of synovitis. Data on demographics, ICI regime, time of onset, imaging and response to therapy of synovitis were prospectively collected. Arthritis was demonstrated in 14 of 16 patients of whom 7 showed monarthritis, 5 had oligoarthritis and 2 had polyarthritis. Patients with ICI-induced arthritis were predominantly male (57%) and seronegative (69%). Regarding the detection of synovitis in staging imaging, moderate sensitivity for contrast-enhanced CT with PET-CT as reference was observed. Disease burden at baseline was high and was significantly reduced after anti-inflammatory treatment. Nine patients were treated with systemic and eight patients with intra-articular glucocorticoids. Six patients who flared on glucocorticoid treatment on tapering were given methotrexate resulting in long-term remission. Patients with synovitis were more likely to have good tumour response. Patients with ICI-induced arthritis were predominantly male and seronegative showing different patterns of arthritis with high disease burden. Good efficacy and safety was observed for methotrexate, particularly for ICI-induced polyarthritis.